2015
DOI: 10.1007/978-3-319-16901-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Importance Measures of Components for Stand-Alone Hybrid Renewable Energy Microgrid

Abstract: This paper presents the results of a new approach on the reliability analyses of standalone hybrid microgrid based on components importance measures. The microgrid presented consists of wind, photovoltaic, diesel generator and energy storage systems for supplying an isolated load. Reliability models of the customers connected to the Microgrid with the mentioned components have been model using a new approach based on reliability block diagram algebra. Different microgrid design structures and component measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Failure of an engineering system is an event after which the system is incapacitated to perform its purpose. Product like bulb once failed cannot be repaired, therefore, repair is only applicable to a system which does not fail ones, and an example of such is a turbo-alternator which can undergo several repairs [6]. Turbo-alternator as a single system has no redundancy built in it and hence has its operational status as either functioning or not, that is, it has 'up' (functioning) or 'down' (breakdown) states as shown in Figure 1.…”
Section: Concept Of Failure and Repairmentioning
confidence: 99%
“…Failure of an engineering system is an event after which the system is incapacitated to perform its purpose. Product like bulb once failed cannot be repaired, therefore, repair is only applicable to a system which does not fail ones, and an example of such is a turbo-alternator which can undergo several repairs [6]. Turbo-alternator as a single system has no redundancy built in it and hence has its operational status as either functioning or not, that is, it has 'up' (functioning) or 'down' (breakdown) states as shown in Figure 1.…”
Section: Concept Of Failure and Repairmentioning
confidence: 99%
“…Isolated loads and rural communities rely on the use of diesel generators for their daily energy needs. Fortunately, some of these places are blessed with renewable energy resources such as wind and solar power [1], [2], [3]. It has been suggested that these renewable energy resources be used to support the existing diesel generator.…”
Section: Genral Introductionmentioning
confidence: 99%